Predicting the short‐ and long‐term effects of recycling organic wastes in cropping systems with the PROLEG tool. (12th November 2022) - Levavasseur, Florent; Houot, Sabine
Abstract: Recycling organic wastes (OWs) in agriculture may increase soil organic carbon (SOC), improve soil chemical, physical and biological properties and make mineral fertilizer savings possible. Some drawbacks are related, for example, to N losses, soil contamination or greenhouse gas (GHG) emissions, and may counterbalance the interest in OW recycling. Some of these effects are only noticeable after repeated applications over several years and depend on OW type, on their insertion in cropping systems (e.g. rate, period) and on pedoclimatic conditions. The optimization of OW recycling should promote its positive effects and limit its negative effects. Various simulation tools can predict some OW effects and help with this optimization. However, despite many existing tools, dedicated tools with a multicriteria approach to OW effects and the ability to consider various OWs, soils, climates and cropping systems are still missing. We developed the PROLEG tool to predict the short‐ and long‐term multiple effects of OW application in agriculture at the field scale. The tool combined the soil‐carbon model AMG to predict SOC changes, the soil‐crop model STICS to predict N supply and N losses, some pedotransfer functions to predict the evolution of some soil properties related to SOC and simple balance equations to predict mineral fertilizer needs, GHG balance, soil contamination with trace metals and economic results. The tool also embedded many parameter tables, especially related to the characteristics of diverse OWs. The tool required easily accessible soil properties and a description of the cropping systems in a simple spreadsheet. It automatically computed mean and detailed output variables in tables and figures. We illustrated the use of the tool with a simple case study. The tool has already been used with farmers to design new cropping systems and to support public policy related to anaerobic digestion.